Sulfated dietary fiber protects gut microbiota from antibiotics - Fuqing Wu; Xiaoqian Annie Yu; David Angeles-Albores; Susan E. Erdman; Eric J. Alm (Microbiome)
Abstract Background Antibiotics, while essential for combating pathogens, also disrupt commensal bacteria, leading to gut microbiota imbalance and associated diseases. However, strategies to mitigate such collateral damage remain largely underexplored. Result In this study, we found that fucoidan, a marine polysaccharide derived from brown seaweed, provides broad-spectrum growth protection against multiple classes of antibiotics for human gut microbial isolates in vitro and for fecal communities ex vivo. This protective effect is dependent on the structural integrity, molecular weight, and sulfur content of the polysaccharide. Transcriptomic analysis showed that while fucoidan had minimal impact on baseline gene expression, it counteracted about 60% of the genes induced by kanamycin, suggesting a potential inhibition of kanamycin. Mass spectrometry results further showed that this inhibition may be due to the non-specific binding of fucoidan to kanamycin in solution. Finally, animal model experiments revealed that fucoidan facilitated the recovery of gut microbes following antibiotic treatment in vivo. Conclusion These findings suggest fucoidan could serve as a potential intervention to help protect gut microbiota during antibiotic therapy. Further studies are needed to evaluate its clinical potential and ensure it does not compromise antimicrobial efficacy. Video Abstract